Application of a finite element model in the diagnosis process of middle ear pathologies - Marin, Karina Cristina (2019)
The ear is a complex organ that can be affected by various pathologies that are still fairly misunderstood. This work tests the possibilities of studying the ear and its pathologies using a virtual environment and thus bypassing expensive and time-consuming clinical trial. A previous validated finite element model of the middle ear was employed to study two pathological states of the middle ear. It was shown that the model obtained results very close to the clinical evaluation thus proving of being a proper tool for further investigations of middle ear pathologies.